Implikasi Hukum Ketidakpatuhan Korea Utara terhadap Resolusi Dewan Keamanan PBB dalam Uji Coba Nuklir - Nuraisah, Nuraisah; Erawaty, Rika (Faculty of Law, Universitas Jambi, 2021)
Since 2006 to 2017 the Security Council has passed a resolution on North Korea's nuclear test act. Article 25 of the UN Charter states that Members of the United Nations agree to accept and implement the decisions of the Security Council in accordance with this Charter. North Korea as a UN member state that obtained the UN Security Council Resolution is obliged to implement the sanctions resolution. However, the sanctions contained in the resolution did not make North Korea stop its nuclear program and it shows North Korea's noncompliance with UN Security Council resolutions. Implications accompanying any denial by North Korea against the UN Security Council resolution which in general affects four fields, namely the fields of economy, politics, defense and international cooperation. In addition to non-military sanctions, the Security Council under chapter VII Article 42 of the UN Charter can impose military sanctions where possible, the Security Council can also impose sanctions through the UN General Assembly on its recommendation to suspend the rights of UN membership) and expulsion of a country from UN membership).